Strategi Manajemen Hubungan Masyarakat dalam Meningkatan Mutu Lembaga Pendidikan di SMP Plus Cordova Banyuwangi - Firdaus, Rifqi (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
The role of school public relations in disseminating information and attracting community participation requires good skills, where the communication messages conveyed can really be known and understood by the community or parents of students so that they get a positive image from the community. Apart from that, public relations has a big role in improving quality, namely by communication both in the form of suggestions and criticism from the public as customers of educational services. This research uses qualitative approach with a descriptive type. Information collection uses observation, interviews with relevant parties and documentation. Data analysis techniques include data condensation, data presentation, and drawing conclusions. The results show that the Community Relations Strategy of SMP Plus Cordova in Improving the Quality of Education, namely: 1) Socializing the School Community, 2) Establishing good relationships with student parents, 3) Establishing connections and building partnerships with related institutions or agencies, 4) Holding a Bazaar Entrepreneurship and Educational Exhibitions, 5) Publicizing Information. Obstacles to Managing Community Relations at SMP Plus Cordova Banyuwangi in Improving the Quality of Education, namely: Social media management on YouTube media and school websites is not yet optimal, management of publications on Instagram and TikTok is not yet optimal. Meanwhile, the Challenges of Managing Community Relations at SMP Plus Cordova Banyuwangi are: There are problems in bridging and cooling parents who want their children to change schools even though their children still want to board and go to school.